An overview of Qur'anic allusions in Iqbal's Urdu poetry - Sabina Awais; Rukhsana Baloch (jihat-ul-islam, 2022)
Iqbal inherited teachings of Islam and love with Quran from his family. His family had great love for religion and nation. Iqbal had shown great love and attachment with Islam and especially with Holy Prophet (S.A.W). Quran has given Iqbal great topics for his philosophical ideas which he interpreted through his poetry. Iqbal strongly believed that Quran is the only factor which creates movement in human nature and enable him to explore new vistas of life. Quran is the only book which bestows right and clear path to human race and provides codes for life. Iqbal spent his life in different environments and faced a lot of difficulties. That change and shift brought many changes in his overall character and changed his view about life. Iqbal used qur’anic versions in his poetry and interpreted qur’anic teachings in a very beautiful way. He tried to implant qur’anic teachings in human nature. This article will encompass Iqbal’s work in the light of the Holy Quran...